Fabrication of Dye Sensitized Solar Cells using Ixora Macrothyrsa. (2021) - Esakki, E. Selva; Sarathi, R.; Sundar, S. Meenakshi; Devi, L. Renuga
Abstract: Dye-sensitized solar cells (DSSCs) were fabricated by ZnO nanoparticles utilizing a solvothermal method so as to improve their efficiencies. In this paper, dye-sensitized solar cells (DSSCs) are designed using natural dyes extracted from the Ixora flower. ZnO nanoparticles are characterized by an X-ray diffractometer, Field Emission Scanning Electron Microscope, UV–Visible, and Fourier Transform Infrared, and Electrochemical Impedance Spectra measurements. The structure and particle size of ZnO were measured by using the X-Ray diffraction technique (XRD). The surface morphology of the prepared sample was investigated using FESEM analysis. From UV–Visible spectra, the bandgap energy of ZnO nanoparticles was measured using the Tauc plot method. Functional group structures of Ixora flowers and ZnO samples have been identified using FTIR. Efficiency for the fabricated cells was decided under 100 mW/cm 2 brightening. DSSC prepared with a dye extracted from red Ixora under 100 mA/W irradiation conditions showed the electrical characteristics: Voc = 0.52 V, Jsc = 1.90 mA/cm 2, Jmp = 0.52 mA/cm 2, Vmp = 0.173 V, FF = 0.089 and ɳ = 0.08%.